Visibility of Acculturation in Legal Translation: Some Remarks about Cadi Ibn Acem ‘s Book Translated into French - بن شريف , محمد هشام (Milev Journal of Research and Studies, 2019)
After French colonialism monopolized Algeria, the French administration faced the problem of establishment judicial institution like courts. Otherwise, there is a great difference between civil law system and Islamic law adopted in Algeria before colonialism. The French administration order their judges to use Islamic law in judging Algerian citizens named « Indigene », by contrast French judges didn’t master both Arabic langue and Islamic law. This is the main reason of appearing legal acculturation by translating into French main books of religious jurisprudence like Mokhtasir Sidi Khalil who explained Imam Malek doctrine .This book was very difficult to understand, as a result two French lawyers decided to translate into French « Tohfa el Hokam » a book written by Cadi Ibn Acen, he was from Andalusia. It’s a judicial book wrote in poetry form addressed to Muslims Cadis and it contained practical steps to rule. This translation made a partial acculturation to French judges and it was a legal and linguistic introduction to Islamic law. In this paper, we are going to give some remarks about French translation of Ibn Acem book containing legal notions originated from Islam religion , and will pay attention for importance of acculturation in legal translation